The Presentation of Speaking Materials in English Textbook for High School Level - Annisrina Fajri Nugraheni; Sindi Dian Safiroh; Putri Rahayu; Putri Widiarsih; Rini Estiyowati Ikaningrum (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2021)
The purpose of this study is to analyze the performance of speaking material in the textbook